Probiotic strain Limosilactobacillus reuteri 29B is proven safe and exhibits potential probiotic traits in a murine vaginal model - Rangasamy, Premmala; Foo, Hooi Ling; Mohd Yusof, Barakatun Nisak; Chew, Shu Yih; Mohd Jamil, Amilia Afzan; Than, Leslie Thian Lung (Springer, 2023)
Lactobacilli, the most common group of bacteria found in a healthy vaginal microbiota, have been demonstrated to act as a defence against colonisation and overgrowth of vaginal pathogens. These groups of bacteria have sparked interests in incorporating them as probiotics aimed at re-establishing balance within the urogenital ecosystem. In this study, the safety characteristics of Limosilactobacillus reuteri 29B (L29B) strain were evaluated through whole genome sequencing (WGS) and animal study. Cell culture assay and 16S rDNA analysis were done to evaluate the ability of the strain to colonise and adhere to the mouse vaginal tract, and RAST analysis was performed to screen for potential genes associated with probiotic trait. The histological study on the mice organs and blood analysis of the mice showed there was no incidence of inflammation. We also found no evidence of bacterial translocation. The cell culture assay on HeLa cells showed 85 of adhesion, and there was a significant reduction of Candida strain viability in displacement assay. As for the 16S rDNA analysis, there was a significant amount of L29B colonisation of the vaginal microflora. Taken together, the intravaginal administration of L29B significantly reduced the number Enterobacteriaceae and Staphylococcaceae that were present in mouse vaginal tract. It also improved and promoted a balanced vaginal microflora environment without causing any harm or irritation to mice. Limosilactobacillus 29B (L29B) is safe to be administered intravaginally.